Analisa Sistem Informasi Akuntansi dan Kualitas Produk UMKM Kabupaten Garut - Irma Rosmayati; Hani Siti Hanifah; Abdul Fatah Hassanudin (Jurnal Kalibrasi, 2023)
The impact of Covid-19 has affected all sectors including MSMEs. Previously, it was estimated that the majority of business actors in our country declined due to the outbreak. This is the concern of all parties, including the atmosphere of higher education. To be able to survive and compete, MSMEs must continue to move and be dynamic in innovation and competence. The purpose of this research is to analyze the accounting information system and product quality of MSME Garut district. A qualitative descriptive research method in which the research collects information about the status of symptoms at the time the research is conducted. The results of the study show that the Accounting Information System plays a role in company decisions, market analysis, financial report analysis in line with the standards for MSME actors and from the government or the Bank. As for the conditions of competitive product marketing, business actors, MSMEs and other producers must strive to improve product quality which will have a positive impact on sales.